Let's analyze the approaches of Esma and Hunter.
The original equation is:
\[ x^2 + 8x = 2x - 8 \]
By subtracting \(2x\) and adding \(8\) to both sides, they rewrote the equation as:
\[ x^2 + 6x + 8 = 0 \]
Esma's Approach: Esma suggests completing the square by adding \(1\) to both sides to rewrite the equation as:
\[ x^2 + 6x + 9 = 1 \]
This can be factored as:
\[ (x + 3)^2 = 1 \]
Then, by taking the square root of both sides, we obtain:
\[ x + 3 = 1 \quad \text{or} \quad x + 3 = -1 \]
This leads to:
\[ x = -2 \quad \text{or} \quad x = -4 \]
Hunter's Approach: Hunter attempts to factor the left-hand side as:
\[ (x + 2)(x + 4) = 0 \]
From this, he would arrive at:
\[ x + 2 = 0 \quad \text{or} \quad x + 4 = 0 \]
This also gives:
\[ x = -2 \quad \text{or} \quad x = -4 \]
Conclusion: Both methods are valid and lead to the same solutions. Therefore, the answer is:
(Choice C) Both